PROSEDUR ANALISIS VALIDASI DELTAMETHRIN PADA PAKAN AYAM MENGGUNAKAN ALAT KROMATOGRAFI CAIR KINERJA TINGGI Penggunaan Kolom C 18, Fase Gerak Asetonitril 80% dalam Akuabides, Laju Alir Fase Gerak 1,25 ml/menit, Panjang Gelombang 236 nm dan Suhu 30 0 C - , ANNISA RAHMAWATI, drh. R. Gagak Donny Satria, M.P., M.Pd. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Currently the use of.HPLC have been widely used to determine pesticides residues due to the simple process with fast analysis time. Food safety factor becomes important as the increasing of consumer awareness to their food quality. The quality of food resources is not only measured from its high nutrient but also free from pesticide. The aim of this study is to validate the deltamethrin analysis procedure on chicken feed by using high-performance liquid chromatography. The deltamethrine concentration used in this research were 1ug/ml, 2 ug/ml, and 5 ug/ml. The main tool used in this study was HPLC Shimadzu 6.1 with a mobile phase 80% acetonitrile in distilled water, mobile phase flow rate of 1.25 ml / min, and a temperature of 30oC. In addition, C 18 column with UV-Vis detector wavelength of 236 nm was used here. Validation parameters used in this study were the specificity, precision, accuracy, detection limit, quantification limit, and linearity. The results showed deltamethrin peak area in HPLC analysis specifically appears within 8 to 9.5 minutes. The mean area of each concentration of 1ug/ml, 2ug/ml and 5ug/ml were respectively 58515.67, 87792.67 and 233404.67. Specificity of each concentration showed good results because the peak area of deltamethrin were undisturbed by other substances. The precision value have a good value due to the results of RSD â¤ 2%. The accuracy value of each concentration fulfill the standards value that are within 80-120%. The detection limit of the instrument has a value of 0.28 ug/ml and for the non instrument does not exist because the area of standard sample can be read. The quantification limit of the instrument has a value of 0.96 ug/ml and for the non-instrument is 0.5 ug/ml. As for the linearity gives an equation y = 44814x + 7100 with a value of R = 0.99. It can be concluded that the procedures used in this study have good validity.